A dataset of healthcare systems for cross-efficiency evaluation in the presence of flexible measure - Abolghasem, Sepideh; Toloo, Mehdi; Amézquita, Santiago (Data in brief, 2019)
This article presents the dataset of the healthcare systems indicators of 120 countries during 2010-2017, which is related to the research article "Cross-efficiency evaluation in the presence of flexible measures with an application to healthcare systems" [1]. The data is collected from the World Bank and selected for the 120 countries. Depending on their role in the performance of the healthcare systems, the indicators are categorized into input (I), output (O) and flexible measure (FM) where the FM measure can play either role of input or output in the healthcare system. The dataset can be used to perform efficiency as well as cross-efficiency analysis of the healthcare systems using methods such as data envelopment analysis (DEA) in the presence of flexible measure.
Keywords: Efficiency measure; Healthcare system; Data envelopment analysis